The Utilitarian Functions and the Nature of Vehicle Inscriptions and Stickers in Southwestern Nigeria - Olusegun A. FANIRAN Faniran; Reuben O. Ikotun; Abiodun Oloyede (Journal of Language and Literature, 2019)
This paper x-rays the utilitarian functions and the nature of vehicle inscriptions and stickers in south-western Nigeria. It traces the history of the use of vehicle writings in Nigeria in general and the southwest in particular chronicling their long history of usage, and noting that it is a common phenomenon nowadays to come across vehicles, most especially commercial ones, heavily bedecked with an array of colourful inscriptions and stickers of different sizes and in different languages and that the posting of the moving emblems on vehicles has become so prevalent and so widespread that there is hardly an automobile on the highways in South-western Nigeria that does not transport them. Our study also reveals that vehicle insignia are meant to serve different purposes some of which include construction of religious messages, moral/philosophical messages, group/individual identity messages, warning and cautionary messages, humours, wits, ribaldry, advertising, politics and public enlightenment messages among several others. Our study further reveals that inscriptions and stickers serve as formidable communicative tools used to transmit diverse messages to the decoders.